Nicotine Dependency and Its Relationship With Emotional Intelligence Among Male Smoker Employees - Shima Yadegar Tirandaz; Mohammad Hasan Sahebihagh; Hossein Namdar Areshtanab; Hossein Jafarizadeh; Mohammad Asghari Jafarabadi (Journal of Research & Health, 2020)
Background: Smoking is one of the most common causes of mortality in the world. Emotional intelligence is the adapting ability to respond to the environment and people appropriately. It plays an important role in various aspects of life such as facing stressful situations and consequently, smoking. This study aimed to investigate the relationship between nicotine dependency and emotional intelligence among male smokers. Methods: This study was conducted on 350 male smokers working at Urmia University of Medical Sciences. The study tools were Cyberia Shrink emotional intelligence questionnaire and Fagerstrom nicotine dependence test. Results: The Mean±SD of nicotine dependency and emotional intelligence were 3.33±2.31 (ranged from 0-10), and 110.26±16.24 (ranged from 33-165), respectively. Overall, the results showed a significant reverse relationship between emotional intelligence and its dimensions with nicotine dependency. Individuals with higher emotional intelligence had a lower degree of nicotine dependency. Conclusion: Emotional intelligence acts as a guard against harmful behaviors such as smoking. Nicotine dependency can be reduced by teaching emotional intelligence skills.